PENGARUH MODEL PEMBELAJARAN PJBL (PROJECT BASED LEARNING) TERHADAP KEMAMPUAN MENULIS TEKS BIOGRAFI KELAS X SEKOLAH MENENGAH KEJURUAN NEGERI 2 KARAWANG TAHUN AJARAN 2017/2018 - Sopiatul Janah; Wikanengsih Wikanengsih; Diena San Fauziya (IKIP Siliwangi, 2018)
This study aims to prove that there is a significant difference in the ability to write biographical texts between classes that apply project-based learning models and classes that do not apply the model. In reaching that goal, the researcher uses an experimental method with Quasi-Experimental Design research form with Nonequivalent Control Group Design research design. The sample used is simple random sampling because sampling is done randomly. In this study, the sample used is class X Accounting 2 as the experimental class amounted to 36 people and X Accounting 1sas control class amounted to 36 people. Based on research which has been done before by researcher, hence the result of research show data among others mean value (mean) end test experiment class equal to 46,25 while control class equal to 39,30. The result of the calculation of the effect size of the text writing capability of the experimental and control class biographies was obtained at 6.95, classified in the high category. So it can be concluded from the data above, that the ability to write a class biography text that applies the model PJBL higher than the ability to write a class biography text that does not apply the model PJBL.